Wages and income impacts of a liberal migration policy: An experimental study - Veronika Mit'ková; Sona Kralova (Naše gospodarstvo / Our Economy, 2023)
This article investigates the impact of a liberal migration policy that increases labour quotas by 5% on wages and income of residents, native migrants, and new migrants. The article focuses on the impact of migration in 21 areas, with particular attention given to Slovakia and Germany. It is based on data collected from the Global Trade Analysis Project database and the experimental design by Walmsley, Ahmed, and Parsons, with adjustments to capture current global migration flows. The findings indicate that the immigration of new unskilled workers negatively impacts the real wages of unskilled residents, decreasing them by almost 3%, while the arrival of skilled workers increases them by 0.73%. Similarly, the real wages of skilled residents decrease by 2.62% due to the arrival of new skilled migrants, while unskilled migration results in its increase by 0.53%. These findings can aid policymakers in developing policies that maximize the benefits of migration. This research provides new insights into the wage effects of migration in different areas, focusing on Germany and Slovakia.
Keywords: C68; J61; J68; 330; CGE Model; Labour migration; Wages; Migrant workers; Labour policy